2015
DOI: 10.3389/fpls.2015.00241
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of transcriptome response to salinity stress in the halophytic turf grass Sporobolus virginicus

Abstract: The turf grass Sporobolus virginicus is halophyte and has high salinity tolerance. To investigate the molecular basis of its remarkable tolerance, we performed Illumina high-throughput RNA sequencing on roots and shoots of a S. virginicus genotype under normal and saline conditions. The 130 million short reads were assembled into 444,242 unigenes. A comparative analysis of the transcriptome with rice and Arabidopsis transcriptome revealed six turf grass-specific unigenes encoding transcription factors. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 83 publications
(108 reference statements)
3
39
0
Order By: Relevance
“…The 2-oxocarboxilic acid pathway is associated with the biosynthesis of amino acids, mainly asparagine and glutamate, that are involved in resistance to abiotic stress through the production of 2-oxoacids (O'Leary et al, 2011). Glutamate is directly associated with abiotic plant responses because it is used as a precursor for production of compatible osmolytes including proline and polyamine (Roberts, 2005;Yamamoto et al, 2015). Additionally, amino acids such as tryptophan and phenylalanine accumulate in maize and wheat under drought stress (Bowne et al, 2012;Witt et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The 2-oxocarboxilic acid pathway is associated with the biosynthesis of amino acids, mainly asparagine and glutamate, that are involved in resistance to abiotic stress through the production of 2-oxoacids (O'Leary et al, 2011). Glutamate is directly associated with abiotic plant responses because it is used as a precursor for production of compatible osmolytes including proline and polyamine (Roberts, 2005;Yamamoto et al, 2015). Additionally, amino acids such as tryptophan and phenylalanine accumulate in maize and wheat under drought stress (Bowne et al, 2012;Witt et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the salt stress response at the molecular level is a possible way to further understand salt tolerance mechanism of bermudagrass. Transcriptome profilings of Kentucky bluegrass, zoysiagrass, and salt couch grass (Sporobolus virginicus) have been analyzed comprehensively, and a number of candidate unigenes related to salt stress responses were identified [49][50][51]; putatively, a total of 36,587, 1455 and 8340 differentially expressed genes were detected for these species, respectively. Functional annotation indicated that the detected genes were related to transcription factors, processes and pathways such as oxidation-reduction process, ion transport and ROS scavenging.…”
Section: Salt Stressmentioning
confidence: 99%
“…(Xie et al 2015) and the highly polyploidy, facultative apomictic Kentucky bluegrass (Poa pratensis L.) (Bushman et al 2016) using transcriptome technology. Furthermore, using these RNA-seq databases, candidate genes involved in salt tolerance have been identified in the halophytic turfgrass Sporobolus virginicus (Yamamoto et al 2015) and in both shoot and root tissues of Kentucky bluegrass (Bushman et al 2016). The protective roles of exogenous melatonin in response to salt stress have been illustrated in the widely planted turfgrass bermudagrass (Cynodon dactylon) (Shi et al 2015).…”
Section: Introductionmentioning
confidence: 99%